China's Carbon-Energy Policy and Asia's Energy Transition Carbon Leakage, Relocation and Halos - Mori, Akihisa (Routledge Contemporary China Series, 2022)
This book seeks to examine the impacts associated with China's carbon-energy policy in Asia and how, coupled with the Belt and Road Initiative, these effects prompt foreign direct investments in coal power and exports of renewable energy technologies. China shows a co-evolution of carbon-energy policy and energy transitions from coal to renewables. Assessing how the policy intensifies pressures and motivations to Chinese companies, chapters in this edited volume analyse how the policy has changed energy and CO2 emissions in Asia through the lens of carbon leakage, relocation, and halos. Contributors present in-depth studies on China's investments and exports, and also its impacts on Indonesia, India, Vietnam, and Japan. Using applied computable general equilibrium and scenario input-output analyses, chapters investigate if regional electricity connectivity reduces new coal power investments through efficiency gain. Arguing that China is shifting from the world's factory to the leading innovator and Asia's demand centre, it is ultimately demonstrated that China is likely to achieve climate targets whereas Asia to increase CO2 emissions and economic reliance on China. China's Carbon-Energy Policy and Asia's Energy Transition will be of significant interest to students and scholars of energy, environment, and sustainability studies, as well as Chinese studies and economics.